Italy : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The Selected Issues paper is focused on policies to secure strong growth and safeguard fiscal sustainability. The paper analyzes the reasons behind Italy's persistent inflation differential vis-a-vis the euro area. It reviews Italy's large regional imbalances through a catch-up in income levels and estimates a growth model using panel data for Italian regions to determine the impact of a number of factors in addition to convergence forces. It also focuses on fiscal sustainability and reviews the case for additional pension reform steps in Italy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet